Vai trò trung gian của năng lực động trong mối quan hệ giữa thông tin kế toán quản trị và lợi thế cạnh tranh: Bằng chứng thực nghiệm tại Việt Nam - Lê Mộng Huyền; Nguyễn Phong Nguyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
Based on the Resource-Based View (RBV) and the Dynamic Capability View, this study develops and tests a multiple mediation model investigating the mediating effect of dynamic capabilities in the relationship between the usage of broad scope management accounting information and competitive advantages. Data analysis results from 240 Vietnamese information technology firms show that broad scope management accounting information has the most substantial impact on change implementation capacity, followed by strategic sense-making capacity, and finally timely decision-making capacity. Strategic sense-making capacity plays a important role in creating cost advantage, while timely decision-making capacity and change implementation capacity play a critical role in creating differentiation advantage. Especially, the research results reveal that dynamic capabilities complementary mediate the relationships between management accounting information and competitive advantages. This study provides theoretical and managerial implications to Vietnamese information technology firms, which are striving to develop management accounting information systems and dynamic capabilities toward enhancing competitive advantages.